MANTRACHIKITSA: FACTS AS MENTIONED IN THE AYURVEDIC CLASSICS - Goswami, Dilip Kr. (International Journal of Research -GRANTHAALAYAH, 2024)
Mantra, indicates chanting of some prescribed verses for designated purposes, is a controversial but interesting and important topic. Scientific validation of mantra is difficult to establish due to the factors like – difficulty in (1) understanding the meaning of the verses, (2) understanding the mode of action, (3) understanding the effect scientifically etc. But traditional experience and classical references strongly support the use and efficacy of Mantra in different references. A number of researches are also already conducted in different levels with the aim to understand it scientifically. In the Ayurvedic classics a number of indications and benefits of Mantra are mentioned in different references like Vishachikitsa (in snakebite mentioned with top priority), Grahachikitsa (conditions that occur due to effect of some unseen, unundentifiable aetiologies etc.). The Ayurvedic scholars have discussed in detail about mantra with special reference to method of learning, practising etc. As a widely discussed noninvasive treatment procedure that is getting topmost priority in a condition like snakebite (a very dangerous and usually fatal poisoning) a discussion on Mantra basing upon the Ayurvedic classics is considered to be informative and thought provoking for the scientific forum.